The rise of person-centered care: Effects of single-room nursing home quotas on long-term care - Annika Herr; Maximilian Lückemann; Arndt R. Reichert (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2025)
This study examines the implications of the rising person-centered care model on the long-term care market, specifically focusing on the promotion of higher single-room occupancy in nursing homes. We exploit the staggered implementation of a state-level policy that requires nursing homes to meet singleroom quotas, forcing many long-term care providers to convert multiresident rooms into singleoccupancy rooms. Our difference-in-differences analyses are based on data from the German Care Statistics covering the period between 2007 and 2019. These data offer detailed insights into the universe of individuals needing care, their specific care arrangements, and all nursing home facilities in the country. Our results indicate that the policy significantly decreases the likelihood of individuals in severe need of care securing a bed in a nursing home. The likelihood of individuals receiving professional home health care remains unchanged by the policy. We observe, however, a notable increase in the proportion of people in severe need of care in informal home care. The policy generates substantial direct net fiscal gains for long-term care insurance and local communities. These likely exceed potential indirect fiscal costs that may arise, for instance, due to reduced income tax revenues for federal and national governments resulting from lower labor supply among informal caregivers.
Keywords: H50; I11; I13; I18; 330; single-room policy; nursing home access; home health care; informal care; difference-indifferences; never treated